2012
DOI: 10.3390/min2010065
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Resources and Production: Critical Assessment and Global Projections

Abstract: This paper critically assesses if accessible lithium resources are sufficient for expanded demand due to lithium battery electric vehicles. The ultimately recoverable resources (URR) of lithium globally were estimated at between 19.3 (Case 1) and 55.0 (Case 3) Mt Li; Best Estimate (BE) was 23.6 Mt Li. The Mohr 2010 model was modified to project lithium supply. The Case 1 URR scenario indicates sufficient lithium for a 77% maximum penetration of lithium battery electric vehicles in 2080 whereas supply is adequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
149
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(151 citation statements)
references
References 7 publications
0
149
0
2
Order By: Relevance
“…With regard to the specific metals, PGM studies have had mixed conclusions with some arguing that supply issues are unlikely to be problematic [27,30], while others have indicated that demand will outstrip supply [28,31], and that in the short term, some challenges with electricity shortages in South Africa have the potential for disruption to supply [31]. In the case of lithium, most studies have indicated that the resources are sufficient for potential future scenarios [39,43]; however, there were some concerns about the physical potential for industry to expand at the required rate [41]. Thin-film solar cells were considered under threat of serious materials supply shortages early on [36], but subsequent analyses have indicated that the likelihood of constrained supply of materials is lowered by the potential for reducing film thicknesses, increasing efficiency, and increasing recycling rates and potential price-induced supply supplementation [35,37,38].…”
Section: Critical Minerals and Unconventional Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the specific metals, PGM studies have had mixed conclusions with some arguing that supply issues are unlikely to be problematic [27,30], while others have indicated that demand will outstrip supply [28,31], and that in the short term, some challenges with electricity shortages in South Africa have the potential for disruption to supply [31]. In the case of lithium, most studies have indicated that the resources are sufficient for potential future scenarios [39,43]; however, there were some concerns about the physical potential for industry to expand at the required rate [41]. Thin-film solar cells were considered under threat of serious materials supply shortages early on [36], but subsequent analyses have indicated that the likelihood of constrained supply of materials is lowered by the potential for reducing film thicknesses, increasing efficiency, and increasing recycling rates and potential price-induced supply supplementation [35,37,38].…”
Section: Critical Minerals and Unconventional Resourcesmentioning
confidence: 99%
“…Important examples have been: neodymium and dysprosium for permanent magnets used in wind turbines and electric vehicles [22][23][24][25]; platinum group metals (PGMs) with particular reference to fuel cell technology [23,[26][27][28][29][30][31]; photo-active materials for thin-film solar cells (cadmium, tellurium, selenium, gallium, indium) [32][33][34][35][36][37][38]; lithium for batteries in electric vehicles [39][40][41][42][43]; rare earth elements (REE) (rare earth elements typically include 17 elements, scandium, yttrium, and the lanthanide series. In the case of this study, the REE of interest are neodymium, dysprosium and yttrium.…”
Section: Critical Minerals and Unconventional Resourcesmentioning
confidence: 99%
“…The client will have the capacity to indicate the ore of the metal and the equipment engaged with mining and handling as model assumptions. [9] They will also have the alternative to choose from a drop down menu or specifically input quantitative information into relevant cells. For instance, area of the brine solution, sort of the brines, kind of equipment, fuel type, will be accessible as drop down menu parameters.…”
Section: Resource Withdrawal Modulementioning
confidence: 99%
“…Great effort has been dedicated to improve the specific energy and power of lithium-ion batteries, while less attention has been directed to aluminum batteries in nonaqueous systems [8]. These systems merit study since aluminum is more abundant (~80,000 ppm), cost-effective, and safer than lithium [9][10][11][12][13]. In addition, the theoretical-specific capacity of aluminum (3.0 Ah g −1 ) is comparable to that of lithium (3.9 Ah g −1 ) [14,15]; unlike lithium, aluminum batteries are not flammable and are not endangered by thermal runaway, which is still a very serious problem of lithium-ion batteries [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of lithium in the earth crust is approximately 20 ppm. The increasing demand of lithiumbased batteries will require additional lithium production and recycling [7]. Great effort has been dedicated to improve the specific energy and power of lithium-ion batteries, while less attention has been directed to aluminum batteries in nonaqueous systems [8].…”
Section: Introductionmentioning
confidence: 99%